A STUDY ON BRAND LOYALTY AMONG MILLENNIALS: STRATEGIES AND INSIGHTS FOR ENGAGING MILLENNIALS - Sharma, Sumit Omprakash; Pandit Mali (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study makes a significant contribution to the fields of brand loyalty and Generation Y (often referred to as Millennials) by investigating strategies to influence loyalty behaviours within this demographic group. Generation Y presents a unique challenge for marketers due to their substantial presence in the market and their tendency to exhibit lower levels of brand loyalty compared to previous generations. This group is also known for its resistance to conventional marketing techniques, which can render traditional strategies ineffective. Despite the growing importance of Generation Y as a key consumer segment, existing literature has yet to fully address the complexities of targeting this demographic. Specifically, there is a lack of comprehensive research on effective tactics for mitigating their perceived disloyalty and adapting marketing strategies to engage them more effectively. In response to these gaps, the study introduces a proposed conceptual model that offers a framework for modifying and enhancing current marketing tools to better resonate with Generation Y. By doing so, the model aims to provide actionable insights into how businesses can improve brand loyalty among this influential group of consumers. This approach seeks to bridge the gap between current marketing practices and the evolving preferences of Generation Y, ultimately helping businesses foster stronger, more enduring connections with this critical market segment.